Role of tyrosine phosphorylation in sperm capacitation / acrosome reaction - Rajesh Preeti B; Naz Rajesh K (BMC, 2004)
Abstract Capacitation is an important physiological pre-requisite before the sperm cell can acrosome react and fertilize the oocyte. Recent reports from several laboratories have amply documented that the protein phosphorylation especially at tyrosine residues is one of the most important events that occur during capacitation. In this article, we have reviewed the data from our and other laboratories, and have constructed a heuristic model for the mechanisms and molecules involved in capacitation/acrosome reaction.